Service Quality, Customer Loyalty and the Mediating Effects of Customer Satisfaction Towards Audit Firms: Perspective of Small-Medium Enterprise (SMEs) Companies in Malaysia - Mohamad Fazzarudin, Mohamad Sabri (2014)
The purpose of this research is to explore the relationship between service quality, satisfaction and loyalty of the client to the audit firms in Malaysia. This paper uses a marketing model, SERVQUAL in order to measure service quality of audit firms in Malaysia. SERVQUAL model was used to measure the perceptions and expectations of small-medium enterprise companies on the services received from audit firms. The five dimensions of SERVQUAL model such as reliability, responsiveness, assurance, tangible and empathy were used to measure the service quality of audit firms. The research was conducted by using primary data. The interview sections were conducted only in area Sungai Petani where they represent two SMEs companies and one for audit firm. Meanwhile, questionnaires were sent to 600 SMEs companies in Malaysia as listed in Companies Commission of Malaysia (CCM) for year 2013. The finding of this study, on average, the small-medium enterprise companies were dissatisfied on all five dimensions of service quality, i.e. reliability, responsiveness, assurance, tangible and empathy. The most dissatisfied dimension was empathy due to clients’ hoped audit firms able to improve and give more individualized attention, caring, provide reliable and prompt services. In addition, customers' satisfaction was found to mediate the relationship of reliability and customer loyalty and partial mediate in dimension of responsiveness. Consequently, the study defines the attributes of the quality services from the clients’ perceptive. As a result, audit firms' needs are more clearly known and with better understanding of their clients. Finally, the audit firms will be in a better position to anticipate client’s requirement and desire rather than to react to clients’ dissatisfaction. In light of this, the results in five dimensions of service quality can be used by audit firms or other managements to perform better in relation to their service quality due to its ability to influence customer satisfaction.